1994
DOI: 10.1177/036354659402200516
|View full text |Cite
|
Sign up to set email alerts
|

Medial Epicondylitis

Abstract: Flexor and extensor muscle-tendon unit activity at the elbow during the golf swing was recorded from subjects with and without medial epicondylitis. There was no significant difference in total swing time between symptomatic (1.23 +/- 0.15 sec) and asymptomatic (1.15 +/- 0.13 sec) subjects nor between golfers with low (1 to 6 handicap, N = 8) and high (11 to 19 handicap, N = 8) scoring abilities. Symptomatic and asymptomatic subjects displayed similar electromyographic profiles for flexor and extensor muscles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…[3] Although injury to the common golf grips on the forces generated in the forearm flexor bundle at the medial epicondyle is commonly muscles. [49] Even though the elbow is a common injury of all elbow injuries, 85% occurred to the lateral site in golfers, little research has been conducted in aspect. In a the devices compared with those that did not use study of golf injuries, McCarroll et al [2] found that them.…”
Section: Elbow Injuriesmentioning
confidence: 99%
“…[3] Although injury to the common golf grips on the forces generated in the forearm flexor bundle at the medial epicondyle is commonly muscles. [49] Even though the elbow is a common injury of all elbow injuries, 85% occurred to the lateral site in golfers, little research has been conducted in aspect. In a the devices compared with those that did not use study of golf injuries, McCarroll et al [2] found that them.…”
Section: Elbow Injuriesmentioning
confidence: 99%
“…The timing and length of the swing phases are used as indices during the swing analysis [ 6 ]. In addition, the golf swing is usually analyzed using the phases and their dividing points [ 7 , 8 ] because these phases have a certain pattern [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“… 12 In addition, the non-dominant arm complex is also influential in generating power in the swing, 14 as the forearm could lead the flexor burst in the acceleration section of the swing. 15 …”
Section: Introductionmentioning
confidence: 99%